Climate change literacy and commitment in Spanish university students. - Almansa-Martínez, Ana María; López Gómez, Sara; Castillo-Esparcia, Antonio (Emerald, 2024)
Purpose – This paper aims to find out if there is a relationship between access to climate change information and student activism. Design/methodology/approach – Exploratory study focused on the survey of 400 [n 5 400] students from 10 universities in Spain from April to May 2022. A questionnaire with 19 questions was divided into blocks of knowledge, awareness, and action and bivariate analysis with a margin of error of ±5% and a confidence level of 95%. Findings –The greater the degree of information received, the greater the activism of university students, who tend to use digital media and social networks to get informed. However, they perceive that the university generates little information and a low number of activities related to climate change. Students demand that universities implement informal, formal, and service-learning environmental education strategies on sustainable consumption. Research limitations/implications – Given the results of previous studies showing the variable “type of degree” does not show differences at the beginning and end of studies, it has not been considered in this research. Nevertheless, it would be convenient to introduce it in future investigations to confirm if this may have an impact on informational habits. Practical implications – This paper urges universities to act as sources of environmental education, given the relationship between the information received and the pro-environmental attitudes of students. Social implications – The universities are powerful social actors that can shape public and political discourses for eco-social transition. Originality/value – This research adds the variable access to information in studies on pro-environmental attitudes. Furthermore, this research provides data about student perceptions of the university, government, industry, and NGO climate actions.
Keywords: Estudiantes universitarios - Opiniones sobre cambios climáticos; Youth; Spain; Universities; Environmental education; Climate change; Climate activism